Contextualization of Islamic Education: Differences in Internalization of Religious Values in Rural and Urban Madrasahs - Mareta, Mira; Muhammad, Muhammad (EDUKASIA, 2022)
The internalization of religious values in adolescents cannot be separated from the religious education process in the environment where the students are located. For this reason, this study aims to explain how to internalize religious values in students in rural and urban Madrasah Aliyahs on Lombok Island. This study employed a descriptive, phenomenological, documentary, and understanding qualitative research approach. To photograph the two poles of two distinct locations, i.e., urban and rural madrasahs on Lombok Island, with specified categories, the study's setting took two extreme points in sampling madrasahs. In-depth interviews, observation, and documentation were used as data collection methods. Purposive sampling, meanwhile, was utilized to select the sources. The findings highlighted that the internalization of religious values was implemented in the classroom learning and religious activities in the madrasahs' internal and external environments. In urban madrasahs, a structural-functional approach with several characteristics was used as a tool for helping students internalize Islamic religious values. Madrasahs in rural regions, on the other hand, put more emphasis on a cultural approach with flexible, dynamic, and adaptive characteristics where education takes into account cultural aspects and societal values. Consequently, a more persuasive approach was applied in rural madrasahs